Effect of Financial Literacy, Capital Capacity, and Network on the Performance of MSMEs in South Tangerang, Banten, Indonesia - Yustisi, Yuni Putri (IJBLE Scientific Publications Community Inc., 2024)
The purpose of this research is to determine how networking, capital capacity, and financial literacy affect the performance of MSMEs in South Tangerang, Banten, Indonesia. The study looks at how these factors relate to MSME performance metrics using a quantitative analysis based on survey data gathered from 120 MSME owners/managers. The findings show a strong positive association between MSME success, networking, capital capacity, and financial literacy. Furthermore, regression analysis shows that improved MSME performance outcomes are linked to increased levels of networking, capital availability, and financial literacy. To support sustainable economic development in the area, our findings highlight the significance of enhancing financial literacy, expanding capital accessibility, and creating networking opportunities for MSMEs in South Tangerang, Banten, Indonesia.